Effect of Volume on Height of Sensory Blockade Keeping Dose Constant with Hyperbaric Bupivacaine in Patients Undergoing Orthopedic Procedure - Farah Naz, Suresh Kumar, Khawaja Kamal Nasir, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the effects of different volumes (2ml-3ml) of hyperbaric bupivacaine as spinal anaesthesia in patients undergoing lower limb orthopaedic procedures. Methodology: Randomized control trial was done at the Department of Anesthesiology and intensive care, PIMS, Islamabad. Two intravenous lines with 18G cannulas were maintained, and patients were preloaded with 1L of ringer-lactate solution. Patients were randomly divided into low volume and high-volume groups. The spinal injection was given in a sitting position with complete aseptic technique, using a 26G spinal needle and the L3-4 interspinous space. In the low volume group, 2 ml of hyperbaric bupivacaine 0.75% was administered, and in the high-volume group, 3 ml of 0.5% hyperbaric bupivacaine was injected in 20 seconds. After the spinal injection, the patient was put in a supine posture with a 5-degree head down. The level of block was assessed with a pin prick at 2 minutes, 10 minutes, and 15 minutes. Data was collected via a study proforma. Results: The mean age of patients was 44.5±8.2 years in group I and 47.7 ± 9.6 years in group II. Males were predominant in both groups. The higher block level was compared among the study groups after 15 minutes. In group I (2 ml 0.75% hyperbaric bupivacaine), 1 (2.9%) had a higher block (above T4), while in group II (3 ml 0.50% hyperbaric bupivacaine), 7 (20.0%) patients were found to have a higher block (above T4) out of the total 35 cases in each group. This difference between the two study groups was statistically significant, as the higher block level was associated with a high volume of hyperbaric bupivacaine (p-0.02). Conclusion: Larger volume of hyperbaric bupivacaine is associated with a higher level of blockade in subarachnoid block for orthopaedic surgical procedures.